Keabsahan Akta Autentik Dalam Pembacaan Akta RUPS Apabila Para Pihak Tidak Mengaktifkan Kamera/Tidak Saling Melihat - Otiana, Komang Utista Cahya; Wisanjaya, I Gede Pasek Eka (Acta Comitas : Jurnal Hukum Kenotariatan, 2023)
In this research, the main objective is to find out the validity of the authentic deed in reading the deed of the General Meeting of Shareholders (GMS) if the parties do not activate the camera or do not see each other. The author uses the application of normative research with a statutory and conceptual approach, the sources of legal materials for this research are primary and secondary sources of legal materials. The author gets the result that the validity of the deed is authentic in the reading of the GMS deed if the parties do not activate the camera or do not see each other. That Article 77 Paragraph (1) of Law of the Republic of Indonesia Number 40 of 2007 which states "besides organizing a GMS as referred to in Article 76, a GMS can also be conducted via teleconference media, video conferences, or other electronic media facilities that allow all GMS participants to see each other and listen directly to and participate in meetings”. Whereas with this matter the implementation of the GMS can be carried out through electronic media such as video conferencing, but if during the implementation there are parties who do not activate the camera due to signal constraints or other matters then this will not cause legal consequences as long as the parties can still hear, see, understand and understand the contents of the deed and the deed is considered as an authentic deed.